A two-scale damage model for high cycle fatigue delamination in laminated composites. (4th December 2015) - Amiri-Rad, Ahmad; Mashayekhi, Mohammad; van der Meer, Frans P.; Hadavinia, Homayoun
Abstract: In this paper a model for predicting fatigue delamination growth in laminated composites under high cycle fatigue is proposed. The model uses the cohesive zone approach and a two-scale continuum damage mechanics model. The behavior of the interface material is considered quasi-brittle at the macro scale while plastic deformations are allowed at the scale of micro-defects. The validity of the proposed model is investigated through several standard tests using experimental data from literature. Good agreement between the numerical and experimental results is observed. The model is also capable of simulating fatigue under variable amplitude loading. This feature of model is shown through several sample simulations.